Pengaruh Variasi Campuran Serbuk Kayu Akasia, Jati, Medang Terhadap Kuat Tekan Beton - Made Sandita Pranatya; Alfath Zain (Institut Teknologi Garut, 2025)
This study aims to evaluate the effect of adding teak, acacia, and medang wood powder on the compressive strength of concrete and its suitability for non-structural applications. This study was conducted experimentally in a laboratory by making cylindrical concrete test specimens and testing their compressive strength after 28 days. Wood powder was mixed into normal concrete with variations of 0% (control concrete), 20%, 40%, and 60%. The test results showed that concrete with a 20% wood powder mixture still met the criteria for non-structural use, with an average compressive strength of 9.60 MPa. However, the addition of large amounts of wood powder (40%–60%) caused a significant decrease in compressive strength, with average values ranging from 6.49 MPa to 4.42 MPa. The control concrete without wood powder showed the best performance with an average compressive strength of 10.79 MPa. These findings indicate that wood powder from Teak, Acacia, and Medang trees can be used as a partial substitute for sand in non-structural concrete mixtures with a maximum usage limit of 20%. The implication is that the use of wood powder at this level not only has the potential to reduce production costs but also helps reduce the need for sand by around 0.93 kg per concrete mixture, thereby contributing to wood waste management and natural resource conservation.